Annual Report of the Investigatory Powers Commissioner 2017 : Including pre-September 2017 oversight by the : Chief Surveillance Commissioner, Intelligence Services Commissioner and Interception of Communications Commissioner /: Including pre-September 2017 oversight by the : Chief Surveillance Commissioner, Intelligence Services Commissioner and Interception of Communications Commissioner. ([2019-03-21]) - Unknown
No abstract available